Begonia titoevangelistae (sect. Baryandra, Begoniaceae) a new species from Catanduanes Island, the Philippines - Tandang, Danilo N.; Rubite, Rosario R.; Angeles Jr., Raul T.; Guzman, Margaret C. De (Phytotaxa, 2016)
Begonia titoevangelistae from Nahulugan Falls, Gigmoto, Catanduanes Island is described as a new species endemic to the Philippines. It resembles Begonia neopurpurea but is distinguished by the variegated leaves where the veins and midrib are dark green to almost black contrasting with light green interveins in the adaxial surface. In the abaxial surface, the veins are maroon contrasting with cream interveins, and its wide obliquely ovate leaf is elongated with shallowly undulate and minutely lobed leaf margin and long acuminate apex. Based on International Union for the Conservation of Nature red list criteria, B. titoevangelistae was assessed to be critically endangered, since it consists of one population with 300 individuals on a 100 m area around the waterfalls, which is being developed into a tourist spot.